New insights into the ferroptosis and immune infiltration in endometriosis: a bioinformatics-based analysis - Liu, Lusha; Han, Feifei; Du, Naiyi; Liu, Yakun; Duan, Aihong; Kang, Shan; Li, Bin (Frontiers in Immunology, 2025)
BackgroundFerroptosis, a recently discovered iron-dependent cell death, is linked to various diseases but its role in endometriosis is still not fully understood.MethodsIn this study, we integrated microarray data of endometriosis from the GEO database and ferroptosis-related genes (FRGs) from the FerrDb database to further investigate the regulation of ferroptosis in endometriosis and its impact on the immune microenvironment. WGCNA identified ferroptosis-related modules, annotated by GO & KEGG. MNC algorithm pinpointed hub FRGs. Cytoscape construct a ceRNA network, and ROC curves evaluated diagnostic efficacy of hub FRGs. Consensus cluster analysis identified ferroptosis subclusters, and CIBERSORT assessed immune infiltration of these subclusters. Finally, RT-qPCR validated hub FRG expression in clinical tissues.ResultsWe identified two ferroptosis modules of endometriosis, and by enrichment analysis, they are closely linked with autophagy, mTOR, oxidative stress, and FOXO pathways. Furthermore, we identified 10 hub FRGs, and the ROC curve showed better predictive ability for diagnosing. RT-qPCR confirmed that the tissue expression of 10 hub FRGs was mostly consistent with the database results. Subsequently, we developed a ceRNA network based on 4 FRGs (BECN1, OSBPL9, TGFBR1, GSK3B). Next, we identified two ferroptosis subclusters of endometriosis and discovered that they are closely linked with endometriosis stage. Importantly, immune enrichment analysis illustrated that the expression levels of immune cells and immune checkpoint genes were significantly different in the two ferroptosis subclusters. Specifically, the ferroptosis subcluster with stage III-IV of endometriosis is more inclined to the immunosuppressive microenvironment.ConclusionsOur study showed that ferroptosis may jointly promote endometriosis progression by remodeling the immune microenvironment, offering new insights into pathogenesis and therapeutics.